THE EFFECT OF EYE EXERCISES ON REDUCING EYE FATIGUE IN ADMINISTRATIVE WORKERS IN THE PLASTIC MANUFACTURING INDUSTRY - Chahyadhi, Bachtiar; Raihan, Ryan; Nugroho, Hengky Ditya Eko (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
The development of technology, especially in the field of information technology, requires individuals to interact with computers. Computers are an important part of several work sectors, especially in the office sector for activities such as entering data, processing data, correspondence activities. The activities of computer user workers require accuracy so that the work requires a long time and detailed vision, so without realizing it can trigger eye disease, namely eye fatigue. Complaints of eye fatigue have symptoms in the form of a throbbing sensation around and behind the eyeball area, double vision, blurred vision, difficulty focusing vision, sore eyes, redness, and watery eyes, headaches accompanied by nausea and dizziness. This study aims to determine the effect of eye exercises on eye fatigue in computer user workers at PT X. This study uses the type of research quasi experiment with non equivalent control group design. Respondents were taken from PT X computer user workers totaling 60 people from a total of 150 employees. The sampling technique used purposive sampling technique. This study used an eye fatigue questionnaire as a research measurement tool by providing eye exercise interventions to the experimental group.The data analysis technique used was the Mann-Whitney Test. The results showed that there was a significant difference in eye fatigue between the experimental group and the control group (p=0.001; p<0.05).